2015
DOI: 10.1021/acs.energyfuels.5b01493
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Fuel Deposition Process of Crude Oil Oxidation in Air Injection

Abstract: Fuel deposition (FD) as an important stage in the oxidation process of the crude oil in air injection technique was less studied in detail as the FD was not obvious in the Thermogravimetry (TG-DTG) experiments in previous study. In this study, the obvious FD in TG-DTG curves and coke formation in the FD process in the isothermal oxidation experiments of the heavy oil were observed.The coke formation and FD characterization of the heavy oil were further investigated using isothermal oxidation experiments and TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…To evaluate the effect of α-Fe 2 O 3 and α-Fe 2 O 3 @OA on heavy oil combustion, porous medium thermo-effect cell (PMTEC) and thermogravimetry–infrared spectroscopy (TG–FTIR) experiments were performed. The PMTEC allows us to evaluate the oxidation process in terms of the thermal effect by directly monitoring the temperature increase. , TG–FTIR allows us to characterize the entire oxidation process using weight loss data, which is very important for the identification of the FD process where cracking/oxidative cracking reactions are dominant. ,, Furthermore, oxidation experiments under isothermal conditions (400 and 500 °C) were also performed. Mössbauer spectroscopy and field emission scanning electron microscopy were employed to analyze the solid residues to determine the possible transformation of α-Fe 2 O 3 and α-Fe 2 O 3 @OA in the combustion process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the effect of α-Fe 2 O 3 and α-Fe 2 O 3 @OA on heavy oil combustion, porous medium thermo-effect cell (PMTEC) and thermogravimetry–infrared spectroscopy (TG–FTIR) experiments were performed. The PMTEC allows us to evaluate the oxidation process in terms of the thermal effect by directly monitoring the temperature increase. , TG–FTIR allows us to characterize the entire oxidation process using weight loss data, which is very important for the identification of the FD process where cracking/oxidative cracking reactions are dominant. ,, Furthermore, oxidation experiments under isothermal conditions (400 and 500 °C) were also performed. Mössbauer spectroscopy and field emission scanning electron microscopy were employed to analyze the solid residues to determine the possible transformation of α-Fe 2 O 3 and α-Fe 2 O 3 @OA in the combustion process.…”
Section: Methodsmentioning
confidence: 99%
“…40,46 TG−FTIR allows us to characterize the entire oxidation process using weight loss data, which is very important for the identification of the FD process where cracking/oxidative cracking reactions are dominant. 14,38,47 Furthermore, oxidation experiments under isothermal conditions (400 and 500 °C) were also performed. Mossbauer spectroscopy and field emission scanning electron microscopy were employed to analyze the solid residues to determine the possible transformation of α-Fe 2 O 3 and α-Fe 2 O 3 @OA in the combustion process.…”
Section: Mossbauer Spectroscopymentioning
confidence: 99%
“…Generally, the reaction process of crude oils can be divided into three different intervals based on TG/DTG curves: low-temperature oxidation (LTO), fuel deposition by coking reactions, and high-temperature oxidation (HTO). 3,7,10,11,25 There are also some studies where only LTO and HTO were reported. 4,20 Before any analysis of reaction intervals and reaction mechanism, it must be mentioned that heating rates had an obvious effect on the temperature range of reaction intervals as reported in other studies, where the different heating rates were used.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the oxidation reactions of crude oils have attracted great attention of scientists from all over the world. In recent years, the oxidation behavior of different crude oils has been widely investigated by thermogravimetry (TG) methods. , In TG experiments, generally a small amount of sample of crude oil, crude oil + sand, or crude oil + rock is loaded into the crucible and heated at the dynamic air flow and a certain heating rate condition until a designed temperature. During the heating process, only the variation of the mass loss is recorded as a function of the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Acceleration of crude oil oxidation by kaolinite's catalytic and surface area effect [10]; • Shifting of oxidation reactions into lower temperature and reduction in activity energy by increased the specific surface area effect of clays [11]; • Enhancement in the deposition and combustion of fuel (coke) by clays [1,12,13]; • Promotion in the LTO of linear alkanes by illite [14]; • Decrease in the apparent activation energy of oxidation reaction of crude oils by clays [15][16][17][18]; • Promotion of fuel formation by carbonate rock [19]; • Reduced activation energy but not affected reaction model by limestone (major calcite + minor dolomite) [20]; • Promotion of LTO with higher oxygen consumption and carbon oxides release by montmorillonite > illite > chlorite > kaolinite [21]; • Increased heat release in LTO by montmorillonite [22]; • Promoting the formation of cribriform structures on asphaltenes surface that aids the combustion of asphaltenes by increasing its surface area by clays (90 wt % kaolinite and 10 wt % illite) [23]; • Merging FD into HTO, shifting reaction intervals (LTO and HTO) into lower temperatures, and significantly reducing activation energy by 54% quartz and 46% mica [24]; • Shift of the reaction intervals into lower temperature and lower activation energy by surface area and catalytic effect of kaolinite, bentonite, and illite [25]; • Clay minerals may be favorable for the combustion of asphaltenes by forming cribriform structures that increase the surface area of asphaltenes [23].…”
mentioning
confidence: 99%